REV-ERB activation as a novel pharmacological approach for treating inflammatory pain - Makhija, Sangeet; Griffett, Joshua D.; Veerakanellore, Giri Babu; Burris, Thomas P.; Elgendy, Bahaa; Griffett, Kristine (Frontiers in Pharmacology, 2023)
Pain is a complex problem affecting millions of people worldwide. The current therapies to reduce pain are limited as many treatment options inadequately address the causes of pain, lead to tolerance of the drug, or have adverse effects including abuse potential. While there are many causes of pain, one underlying mechanism to the pathogenesis and maintenance of pain conditions is chronic inflammation driven by the NLRP3 inflammasome. Several inflammasome inhibitors are currently under investigation however have the potential to suppress the functioning of the innate immune system, which may cause unwanted affects in patients. Here, we show that the nuclear receptor REV-ERB can suppress the activation of the inflammasome when pharmacologically activated with small molecule agonists. Additionally, REV-ERB activation appears to have analgesic potential in a model of acute inflammatory pain, likely as a result of inflammasome suppression.